Cover Image, Volume 120, Number 11, November 2019. Issue 11 (13th September 2019) - Touyama, Kenya; Khan, Masud; Aoki, Kazuhiro; Matsuda, Miho; Hiura, Fumitaka; Takakura, Nana; Matsubara, Takuma; Harada, Yui; Hirohashi, Yuna; Tamura, Yukihiko; Gao, Jing; Mori, Kayo; et al.
Abstract : Front Cover : The cover image is based on the RESEARCH ARTICLE Bif‐1/Endophilin B1/SH3GLB1 regulates bone homeostasis by Kenya Touyama et al., https://doi.org/10.1002/jcb.29193 . Cover Credit : Cover image © Eijiro Jimi Images